PARAMETRIC STUDY OF LAMINAR FREE CONVECTION IN INCLINED POROUS ANNULUS WITH FINS ON THE INNER CYLINDER - Saad M. AL-Mashaat; Manal H. AL-Hafidh (Journal of Engineering, 2023)
An experimental and numerical study has been carried out to investigate the heat transfer by natural convection in a three dimensional annulus enclosure filled with porous media (silica sand) between two inclined concentric cylinders with (and without) annular fins attached to the inner cylinder under steady state condition; The experiments were carried out for a range of modified Rayleigh number (0.2 ≤Ra*≤ 11) and extended to Ra* =500 for numerical study, annulus inclination angle of (δ = 0˚, 30˚, 60˚ and 90˚). The numerical study was to write the governing equation under an assumptions used Darcy law and Boussinesq’s approximation and then solved numerically using finite difference approximation. It was found that the average Nusselt number depends on (Ra*, Hf, δ and Rr) and the maximum value of the local Nusselt number for vertical cylinder is about two times as large as that of the horizontal case. The results showed that, increasing of fin length increases the heat transfer rate for any fins pitch unless the area of the inner cylinder exceeds that of the outer one, then the heat will be stored in the porous media. A correlation for Nu in terms of Ra, Rr and δ, has been developed for inner cylinder. A comparison was made between the results of the present work and with other researches for the case without fins and excellent agreement was obtained and reveals deviation less than 5 % for average Nusselt number.